The effect of financial deregulation on money demand in Malaysia / Mahyudin Ahmad - Ahmad, Mahyudin (2008)
The study seeks to examine the impact of financial deregulation on the money demand in Malaysia and the implication of altered money demand pattern on the Malaysian monetary conduct. It also attempts to investigate the currency substitution effect as a result of the financial market development and integration of domestic market with the rest of the world. The study utilizes Augmented Dickey Fuller (ADF) and Phillips Perron (PP) tests for unit root and stationarity of data, multivariate Johansen cointegration test, and Vector Error Correction model in an analysis of the dynamics of the short run money demand model and adjustment to restore its long run equilibrium. Findings suggest a stable long run relationship of money demand in Malaysia and a greater income elasticity of money demand supported by growing degree of monetization. In addition, they also suggest a substantial improvement in banking infrastructure as well as some degree of currency substitution among domestic residents. However, short run dynamic of money demand is found to be instable and correction of its disequilibrium over time was somehow slow, hence shifting monetary targeting by authority from monetary aggregates towards interest rates.